2018
DOI: 10.3390/mti2040068
|View full text |Cite
|
Sign up to set email alerts
|

Takeover Requests in Highly Automated Truck Driving: How Do the Amount and Type of Additional Information Influence the Driver–Automation Interaction?

Abstract: Vehicle automation is linked to various benefits, such as increase in fuel and transport efficiency as well as increase in driving comfort. However, automation also comes with a variety of possible downsides, e.g., loss of situational awareness, loss of skills, and inappropriate trust levels regarding system functionality. Drawbacks differ at different automation levels. As highly automated driving (HAD, level 3) requires the driver to take over the driving task in critical situations within a limited period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…References [4,11,13,16,18] report a degree of certainty (uncertainty information) with which the automation can cope with the current scenario as relevant. Additionally, it has been reported that the remaining automated travel distance/time is important [11,[19][20][21]. These information requirements have already been incorporated into the HMI design for partially and conditionally automated driving in numerous studies (e.g., [12,14,[22][23][24]).…”
Section: Information Needs In Automated Drivingmentioning
confidence: 99%
See 1 more Smart Citation
“…References [4,11,13,16,18] report a degree of certainty (uncertainty information) with which the automation can cope with the current scenario as relevant. Additionally, it has been reported that the remaining automated travel distance/time is important [11,[19][20][21]. These information requirements have already been incorporated into the HMI design for partially and conditionally automated driving in numerous studies (e.g., [12,14,[22][23][24]).…”
Section: Information Needs In Automated Drivingmentioning
confidence: 99%
“…Therefore, participants wanted to have an overview of this intersection. In the context of the navigation data, a display of the remaining automated travel time/distance was mentioned only three times, and, in contrast to the literature [11,[19][20][21], had only a subordinate role. On the one hand, this may be due to the fact that there were no interruptions due to requests to intervene, and, on the other hand, no free NDRAs were offered which might have required better planning via the remaining time.…”
Section: Need For Informationmentioning
confidence: 99%
“…Studies actually investigating design and effects of predictive HMI elements were conducted by Richardson et al [14], Wandtner et al [15], and Holländer et al [12]. All three studies found positive effects; Richardson et al [14] discovered time-and distance-based predictive HMIs for conditionally automated trucks to lower workload, and increase acceptance and usability compared to a baseline HMI with no predictive elements. No difference was found between the predictive HMIs.…”
Section: Introductionmentioning
confidence: 99%
“…However, post-study questions revealed distance-based HMI to be the favorite. Richardson et al [14] assume the professional truck drivers' background to be the reason for this preference. Positive effects on usability were also found by Holländer et al [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation